The Effect of Marketplace and Social Media as a Marketing Strategy on the Expansion of Creative Industry Market Segments - Andhika Purnomo Wibowo; Wijiastuti, Sri Wijiastuti; Widodo, Zandra Dwanita Widodo (International Journal of Asian Business and Management, 2023)
This study aims to determine: (1) The effect of the marketplace on market segment expansion, (2) The effect of social media on market segment expansion (3) The effect of marketplace and social media on market segment expansion. This research is a quantitative type with data analysis techniques using multiple linear regression. The sample in this study will be selected using a purposive sampling technique. The sample in this study was 50 respondents who were MSME actors in the Pottery Creative Industry in Paseban Village, Klaten Regency. From the simultaneous test (Test F) which shows that there is a significant influence between Marketplace and Social Media on Market Segment Expansion. Based on the test of the coefficient of determination (R2), the Adjusted R Square value shows a result of 0.841. This means that the Market Segment Expansion variable is influenced by Marketplace and Social Media variables by 84.1% while the remaining 15% market segment expansion is influenced by other variables not included in this study